2020
DOI: 10.3390/bs10110174
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Workload and Work Flexibility on Work-Life Conflict and the Role of Emotional Exhaustion

Abstract: The purpose of this study is to examine the relationship between contextual work-related factors in terms of job demands (workload—WL) and job resources (work flexibility—WF), work–life conflict (WLC) and the burnout dimension emotional exhaustion (EE) in a large population-based sample. Building on the job demands resources model (JDRM), we have developed the hypothesis that WL has an indirect effect on EE that is mediated by WLC. We conducted a secondary analysis using data from the Dresden Burnout Study (DB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…The present results are in line with studies finding long working hours to be a predictor for exhaustion, particularly in mobile-flexible employees (Graf, 2018;Rafnsdóttir & Heijstra, 2013). Interestingly, the study of Buruck et al (2020) highlights that workload had a significant positive relation to exhaustion but a negative relation to work flexibility. This finding could explain the mixed evidence in the literature regarding mobile-flexible working arrangements as well as the impact of A-FO designs on mental health (Bodin Danielsson & Theorell, 2019;Colenberg et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present results are in line with studies finding long working hours to be a predictor for exhaustion, particularly in mobile-flexible employees (Graf, 2018;Rafnsdóttir & Heijstra, 2013). Interestingly, the study of Buruck et al (2020) highlights that workload had a significant positive relation to exhaustion but a negative relation to work flexibility. This finding could explain the mixed evidence in the literature regarding mobile-flexible working arrangements as well as the impact of A-FO designs on mental health (Bodin Danielsson & Theorell, 2019;Colenberg et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…In a cross-sectional study, Buruck et al (2020) show that increased workload is related to increased exhaustion in mobile-flexible employees. This finding is closely linked to Sonnentag`s (2018) recovery paradox, which states that workers in stressful occupations are more likely to work during non-working time and be consistently available on their mobile devices (Bliese et al, 2017;Demerouti et al, 2014;Eurofound, 2020;Sonnentag, 2018).…”
Section: Long Working Hours and Exhaustion Among Mobile-flexible Empl...mentioning
confidence: 99%
“…Previous research found that life satisfaction, particularly JS [63], is associated with a range of long-term work-life conflicts [69,70]. Compared to other types of life dissatisfaction, job dissatisfaction is known to have a stronger association with depressive symptoms [56].…”
Section: Discussionmentioning
confidence: 98%
“…As previously proposed, the resource occupation of subordinates’ relational crafting will inevitably and significantly reduce their resources to enact other formally prescribed behaviors as resources are finite, and thus increase their subjective job stress, work pace, and perceived assignments, thereby enhancing work load and reducing well-being. Prior research also indicated that excessive work load not only had a negative effect on job status and job satisfaction ( Kunte et al, 2017 ; Mittal and Bhakar, 2018 ; Hwang et al, 2020 ) but was also positively related to job burnout and emotional exhaustion ( Weigl et al, 2016 ; Buruck et al, 2020 ). Therefore, we hypothesize the following:…”
Section: Theory and Hypothesesmentioning
confidence: 97%